A key to the Russian species of the genus Coenosia Meigen (Diptera, Muscidae), with the description of one new species and new synonymies - Sorokina, Vera S. (Zootaxa, 2023)
Identification keys to males and females are provided for the 77 species of the genus Coenosia Meigen, 1826 known from Russia, including one new species from the Magadan region (Coenosia luxia sp. nov.), and also Macrorchis meditata (Fallén, 1825). Coenosia nevadensis Lyneborg, 1970 and Coenosia penicillata Hennig, 1961 are newly recorded in Russia. Coenosia paludis Tiensuu, 1939 and Coenosia ukokensis Sorokina, 2009 are newly recorded for the Far East. Two new synonymies are proposed: Hoplogaster morrisoni Malloch, 1924 syn. nov. of Anthomyza cingulipes Zetterstedt, 1849; Coenosia brevicauda Pont in Pont, Werner & Kachvoryan, 2005 syn. nov. of Coenosia nevadensis Lyneborg, 1970. Images of some species and of the male terminalia are given.